Methodology for selecting objects for reverse engineering at oil and gas industry enterprises - Zhukov Aleksandr; Berkutova Tatiana; Zhurenkov Denis; Kolosov Aleksandr; Kheruvimova Svetlana; Kartsan Igor (E3S Web of Conferences, 2024)
The basic methods of reengineering and the possibility of their application at the enterprises of both oil and gas industry and enterprises of defense-industrial complex under the conditions of ensuring technological independence are presented. The methodology of justification of selection of objects for reverse engineering at the presented enterprises has been developed, including the following criteria: participation of the reverse engineering object in the production of special products, reduction of unit production costs when implementing the reverse engineering object, the share of revenue from products containing the object in the total revenue of the enterprise, the level of import-independence provided by the reverse engineering object. For each criterion, verbal-numerical scales are developed, a complex coefficient is proposed, the values of which are used in making managerial decisions justifying the choice of objects for reverse engineering.